Development And Performance Of Turbocharger Based Micro Gas Turbine System Using Biomass Fuel - Al-Attab, Khaled Ali Mohammad (2011)
Alternative fuels are a priority in energy research field, due to issues of fossil fuel depletion and environmental degradation. Biomass is an important renewable energy fuel source for thermal and power applications, especially in countries like Malaysia where abundant biomass waste available. As for electrical power generation, interest has recently increased in small scale distributed generation (DG) due to its advantages over centralized power generation. Internal combustion (IC) engines, micro gas turbines (MGT) and wind turbines are the main candidates for DG technology. Biomass gasifiers with IC engines have shown success for power generation. However, one of the problems with these systems is the maintenance requirement, since producer gas has to be cleaned, cooled and dried before it can be used in IC engines.